Exploring the mechanisms of Qingdu Fang for the treatment of cervical HR-HPV using UPLC-QTOF-MS, network pharmacology, and cell experimentation - Wang, Shanyun; Li, Guangru; Wang, Zhuqiang; Luo, Qing; Zeng, Jianfeng; Xiao, Jing (Frontiers in Pharmacology, 2024)
Background: Qingdu (QDF) is a traditional Chinese herbal formula with remarkable clinical effect in the treatment of HR-HPV, but its mechanism remains unclear.In this study, UPLC-QTOF-MS was used to detect its components, network pharmacology was used to explore the traditional Chinese medicine monomers and their related targets for the treatment of HR-HPV in QDF. Molecular docking and in vitro experiments were performed to verify the results.Methods:QDF constituents and active compounds were identified using UPLC-QTOF-MS analysis. TCMSP and GeneCard databases were used to identify active components, targets, and potential therapeutic targets in HR-HPV. PPI network was constructed using the String database to analyze protein-protein interactions.Cytoscape3.7.2 was used to construct PPI networks, while GO enrichment and KEGG pathway analyses with R. The effect of QDF on H8 cell proliferation was measured using the CCK-8 method, and apoptosis and cell cycle was assessed with flow cytometry. The effects of QDF on PI3K/AKT pathway were detected by Western blotting.Results:A total of 27 compounds were identified on QDF by UPLC-QTOF-MS. Base on Network pharmacology,a total of 254 target genes are involved in the action of QDF on cervical HR-HPV. PPI analysis suggested that TP53, JUN, AKT1, STAT3, TNF and IL6 were potential targets for QDF treatment of HR-HPV.Molecular docking shows that two compounds have strong binding activity with AKT1.CCK-8 and morphological observation have shown that QDF inhibits H8 cell proliferation in a dose-dependent manner.Flow cytometry experiments suggest that QDF induces apoptosis and cell cycle arrest in H8 cells. Western blotting experiments reveal that QDF inhibits the PI3K/AKT signaling pathway.Conclusions:QDF has a multi-faceted therapeutic approach for HR-HPV, targeting inflammation, oxidation, and apoptosis. It induces apoptosis in H8 cells by inhibiting the PI3K/AKT pathway.